Occurrence of gastrointestinal parasites in dogs in a rural area of Santa Catarina, Brazil - Arruda, Alisson Andrade; Bresciani, Katia Denise Saraiva [UNESP]; Werner, Simone Silmara; da Silva, Bruna Fernanda (FapUNIFESP (SciELO), 2023)
We investigated the occurrence of gastrointestinal parasites in dogs in rural areas of the municipality of Painel, Santa Catarina, Brazil. For this, 91 canine feces samples were collected from 82 farms between August, 2017 and January, 2018. These fecal materials were processed using the techniques of spontaneous sedimentation, centrifugation-floatation in zinc sulfate and Ziehl-Neelsen staining. A questionnaire in the form of an interview was administered to the dogs’ owner and information about the farm and the main care provided for the dogs was obtained. Among 91 sampled dogs, 27 (29.7%) were positive for at least one parasite species. Ancylostoma was the most prevalent genus (16.5%), followed by Giardia duodenalis (14.3%), Trichuris vulpis (6.6%), Toxocara canis (5.5%), Entamoeba spp. (4.8%), Cryptosporidium spp. (3.3%) and Taeniidae (1.1%). Most dogs do not receive veterinarian care and rarely received antiparasitic treatment. They were free to roam and had free access to animal remains and garbage, which was reflected in the significant associations with the occurrence of parasites that were found. We conclude that rural dogs harbor gastrointestinal parasites, but that their owners are unaware of the risks that these parasites can bring to human health.
Ocorrência de parasitas gastrintestinais em cães de área rural de Santa Catarina, Brasil
Keywords: Dogs; helminths; microscopy; Protozoa; public health; zoonoses